2018
DOI: 10.1186/s13014-018-0997-y
|View full text |Cite
|
Sign up to set email alerts
|

In silico assessment of the dosimetric quality of a novel, automated radiation treatment planning strategy for linac-based radiosurgery of multiple brain metastases and a comparison with robotic methods

Abstract: BackgroundTo appraise the dosimetric features and the quality of the treatment plan for radiosurgery of multiple brain metastases optimized with a novel automated engine and to compare with plans optimized for robotic-based delivery.MethodsA set of 15 patients with multiple brain metastases was selected for this in silico study. The technique under investigation is the recently introduced HyperArc. For all patients, three treatment plans were computed and compared: i: a HyperArc; ii: a standard VMAT; iii) a Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 29 publications
(15 reference statements)
0
29
1
Order By: Relevance
“…With the recent introduction of commercial single‐isocenter planning algorithms for simultaneously treating multiple brain metastases, either using automated dynamic conformal arcs or automated VMAT, more dosimetric comparison to GK is required. These studies have already demonstrated a reduction in monitor units compared with conventional VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent introduction of commercial single‐isocenter planning algorithms for simultaneously treating multiple brain metastases, either using automated dynamic conformal arcs or automated VMAT, more dosimetric comparison to GK is required. These studies have already demonstrated a reduction in monitor units compared with conventional VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…These structures were used for collimator angle optimization. Arc geometry (four arc fields; one full coplanar arc with a 0° couch and three half noncoplanar arc fields a 315°, 45°, and 90° or 270° couch) arranged with a single isocenter automatically located on the basis of the distance between each lesion . The prescription dose was the same as that of the clinical treatment plan for 95% volume of the PTV all , and 6‐MV flattening filter‐free photon beams were used.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 7 compares the PCI of this study with the historical data from other institutes and modalities such as LINAC circular and mMLC, 18 Cyberknife, 19 Gamma Knife, and RapidArc. 20 The V12, PCI, and mGI have been reported as key indicators for brain toxicities, 1-3 such as radionecrosis, etc.…”
Section: Discussionmentioning
confidence: 99%